Hubungan Beban Kerja Perawat Dengan Upaya Pencegahan Hais Pada Masa Pandemi Covid 19 di Rumah Sakit Pertamina Bintang Amin Bandar Lampung - Triyoso Triyoso; Dewi Kusumaningsih; Respa Agustina Anggara (Universitas Malahayati Lampung, 2022)
ABSTRACT: RELATIONSHIP OF NURSES WORKLOAD WITH HAIS PREVENTION EFFORT DURING THE COVID-19 PANDEMIC AT PERTAMINA BINTANG AMIN HOSPITAL BANDAR LAMPUNG Introduction: The incidence of menstruation is still high, one of the factors is the relatively high workload of nurses. excessive workload on nurses can trigger stress and burnout. Nurses who experience stress and burnout allow them to not be able to perform effectively and efficiently because their physical and cognitive abilities are reduced which may occur due to an imbalance between the number of patients and the number of nurses working in the hospital. Based on the results of the pre-survey, the comparison of the workload of nurses at Pertamina Bintang Amin Hospital Bandar Lampung and dr. A. Dadi Tjokrodipo by distributing questionnaires to 15 nurses in each hospital. At the hospital. Pertamina Bintang Amin showed that nurses experienced a physical workload of 7 nurses (46.6%) with a score of 27-54, and a mental workload of 8 nurses (53.3%) with a score of 57. Meanwhile, RSUD dr. A. Dadi Tjokrodipo, the results showed that nurses experienced a physical workload of 5 nurses (33.3%) with a score of 27-54, and a mental workload of 6 nurses (40%) with a score of 57.Objective: to find out the relationship between the workload of nurses and efforts to prevent HAIs during the Covid 19 pandemic at Pertamina Bintang Amin Hospital Bandar Lampung in 2021Methods: This type of research is a quantitative, cross-sectional design. The population and sample were 110.1 respondents, which were rounded up to 111 respondents. The sampling technique was purposive sampling, data analysis using univariate and bivariate using chi-square test.Results: The physical workload of nurses as many as 57 respondents (51.4%) experienced a high physical workload. The mental workload of nurses as many as 61 respondents (55.0%) experienced a high mental workload. Efforts to prevent HAIs during the Covid 19 pandemic were 64 respondents (57.7%) with bad HAIs prevention. The results of the analysis using chi-square, obtained P-Value = 0.000 so that P-Value α (0.000 0.05), it can be concluded that there is a relationship between the physical workload of nurses and efforts to prevent HAIs during the covid 19 pandemic. The results of the analysis using chi-square, obtained P-Value = 0.015 so that P-Value α (0.0000.05), it can be concluded that there is a relationship between the physical mental workload of nurses and efforts to prevent HAIs during the covid 19 pandemic.Suggestion: Hospitals as a place for health services should pay attention to the welfare of nurses by increasing the medical team, and paying attention to BOR to prevent physical and mental workloads. Keywords: Nurse Workload, Efforts to Prevent Menstruation, Covid 19 Pandemic INTISARI: HUBUNGAN BEBAN KERJA PERAWAT DENGAN UPAYA PENCEGAHAN HAIS PADA MASA PANDEMI COVID 19 DI RUMAH SAKIT PERTAMINA BINTANG AMIN BANDAR LAMPUNG Pendahuluan: Angka kejadian hais masih tinggi salah satu faktor nya adalah beban kerja perawat yang relatif tinggi. Beban kerja yang berlebih pada perawat dapat memicu timbulnya stres dan burnout. Perawat yang mengalami stres dan burnout memungkinkan mereka untuk tidak dapat menampilkan performa secara efektif dan efisien dikarenakan kemampuan fisik dan kognitif mereka menjadi berkurang yang kemungkinan dapat terjadi disebabkan karena ketidakseimbangan antara jumlah pasien dengan jumlah perawat yang bekerja di rumah sakit tersebut.Berdasarkan hasil Prasurvey perbandingan beban kerja perawat di Rumah Sakit Pertamina Bintang Amin Bandar Lampung dan RSUD dr. A. Dadi Tjokrodipo dengan cara melakukan penyebaran kuesioner kepada 15 perawat di masing-masing Rumah Sakit. Pada RS. Pertamina Bintang Amin diperoleh hasil perawat mengalami beban kerja fisik sebesar 7 perawat (46,6%) dengan skor nilai 27-54, dan beban kerja mental sebesar 8 perawat (53,3%) dengan skor nilai 57. Sedangkan RSUD dr. A. Dadi Tjokrodipo diperoleh hasil perawat mengalami beban kerja fisik sebesar 5 perawat (33,3%) dengan skor nilai 27-54, dan beban kerja mental sebesar 6 perawat (40%) dengan skor nilai 57.Tujuan: diketahui hubungan beban kerja perawat dengan upaya pencegahan HAIs pada masa pandemi Covid 19 di Rumah Sakit Pertamina Bintang Amin Bandar Lampung Tahun 2021Metode: Jenis penelitian kuantitatif, rancangan Cross Sectional. Populasi dan sampel 110,1 responden, yang dibulatkan menjadi 111 responden, teknik sampling purposive sampling, analisa data menggunakan univariat dan bivariat menggunakan uji chi square.Hasil : Beban kerja fisik perawat sebanyak 57 responden (51,4%) mengalami beban kerja fisik tinggi. Beban kerja mental perawat sebanyak 61 responden (55,0%) mengalami beban kerja mental tinggi. Upaya pencegahan HAIs pada masa pandemi Covid 19 sebanyak 64 responden (57,7%) dengan pencegahan hais baik. Hasil analisa menggunakan chi-square, didapat P-Value = 0,000 sehingga P-Value α (0,0000,05) maka dapat disimpulkan terdapat hubungan beban kerja fisik perawat dengan upaya pencegahan HAIs pada masa pandemi covid 19. Hasil analisa menggunakan chi-square, didapat P-Value = 0,015 sehingga P-Value α (0,0000,05) maka dapat disimpulkan terdapat hubungan beban kerja fisik mental perawat dengan upaya pencegahan HAIs pada masa pandemi covid 19.Saran : Rumah Sakit sebagai tempat pelayanan kesehatan, sebaiknya memperhatikan kesjahteraan perawat dengan cara memperbanyak tim medis, dan memperhatikan BOR guna mencegah terjadinya beban kerja fisik dan mental. Kata Kunci: Beban Kerja Perawat, Upaya Pencegahan Hais, Pandemi Covid 19